2012
DOI: 10.1002/cvde.201207006
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Sc2O3‐Stabilized Zirconia Obtained by MOCVD as a Potential Electrolyte for Solid Oxide Fuel Cells

Abstract: Dense, crack-free thin films (<5 mu m) of the nanostructured scandia-zirconia system (Sc2O3:ZrO2) stabilized in the cubic-fluorite phase (c-ZrO2) are deposited through conventional low-pressure metal-organic(LP-MO) CVD by using beta-diketonate metal complexes as precursors [(Zr(tmhd)4 and Sc(tmhd)3, with tmhd?=?2,2,6,6-tetramethyl-3,5-heptanedionate]. The compositional (energy dispersive X-ray spectroscopy EDX), structural (X-ray diffraction XRD) and morphological (field emission gunenvironmental scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…However, 8ScSZ thin films were not fully stabilized in the cubic structure, which have a minor tetragonal phase according to the XRD patterns. The cross-sectional scanning electron microscopy (SEM) micrographs of the 8ScSZ thin films confirmed crack-free, thick, and dense coatings adherent to Al 2 O 3 and NiO/YSZ porous substrates [101]. The electrical properties of 8ScSZ thin films on Al 2 O 3 substrates were investigated and the results showed activation energy of 1.09 eV for oxygen ion diffusion and ionic conductivity of 0.002 S cm À1 at 600 C. The ionic conductivity of 8ScSZ at 600 C is twice that of 13 mol% yttria-stabilized zirconia (13YSZ) prepared in the same manner [101], which is consistent with the ionic conductivity enhancement observed for ScSZ compared to YSZ with the different synthesis routes [79].…”
Section: Scandia-stabilized Zirconiamentioning
confidence: 88%
See 2 more Smart Citations
“…However, 8ScSZ thin films were not fully stabilized in the cubic structure, which have a minor tetragonal phase according to the XRD patterns. The cross-sectional scanning electron microscopy (SEM) micrographs of the 8ScSZ thin films confirmed crack-free, thick, and dense coatings adherent to Al 2 O 3 and NiO/YSZ porous substrates [101]. The electrical properties of 8ScSZ thin films on Al 2 O 3 substrates were investigated and the results showed activation energy of 1.09 eV for oxygen ion diffusion and ionic conductivity of 0.002 S cm À1 at 600 C. The ionic conductivity of 8ScSZ at 600 C is twice that of 13 mol% yttria-stabilized zirconia (13YSZ) prepared in the same manner [101], which is consistent with the ionic conductivity enhancement observed for ScSZ compared to YSZ with the different synthesis routes [79].…”
Section: Scandia-stabilized Zirconiamentioning
confidence: 88%
“…Thus, we will discuss the studies reported in the literature for <10 μm thick ScSZ films. These thin film electrolytes have been grown by chemical vapor deposition [101], wet powder spraying [102], electrostatic spray deposition [103], sol-gel deposition [104], dip coating [105], drop-coating [106], pulsed laser deposition [107], and molecular beam epitaxy [58] techniques. The results of these studies will be summarized in this section including theoretical simulation studies on SCSZ.…”
Section: Scandia-stabilized Zirconiamentioning
confidence: 99%
See 1 more Smart Citation
“…In work [ 32 ], ScSZ and Al 2 O 3 -doped ScSZ layers were synthesised by the MOCVD method in the presence of plasma. Interesting results were obtained in the work [ 43 ], where ScZ layers were deposited on porous substrates using this technique.…”
Section: Introductionmentioning
confidence: 99%